Structural interventions on the drums of the Parthenon’s north colonnade (Fracture and Structural Integrity, 2017)
The Acropolis monuments are globally recognized as a cultural heritage and a value belonging not only to Greece but also to Humanity. From 2000 the most recent phase of restoration in their history began by the “Acropolis Restoration Service” (YSMA), introducing new, pioneering methods, recognized now worldwide. Especially the restoration of the Parthenon’s North Colonnade is an enormous work-plan to be carried out (extended area of intervention, great number of members to be restored and high degree of damages). Moreover, the structural stability of the Parthenon’s north colonnade is among the most important challenges confronted by experts working in this sector. The complexity of this effort (a combination of scientific research and direct field application) makes the implementation of the restoration project difficult, rendering its division into smaller projects (for similar structural members) a necessity. In this direction, characteristic examples of the procedure followed for the structural intervention on the drums are presented in this paper. Each member’s report includes a short history of its restoration, the intervention steps, pictures/sketches and the methodology chosen for its structural study, focusing on the particularities of the member and the in-field realization.
Keywords: Classical Monuments; Drums; Fracture; Restoration; Titanium reinforcement; Parthenon; Acropolis of Athens